2022
DOI: 10.1140/epjc/s10052-022-10617-1
|View full text |Cite
|
Sign up to set email alerts
|

Superradiance scattering off Kerr-like black hole and its shadow in the bumblebee gravity with noncommutative spacetime

Abstract: We consider a bumblebee gravity-based Kerr-like black hole in a noncommutative (NC) background and study the superradiance effect and the shadow cast. We extensively study the different aspects of the black hole associated with a generalized Kerr-like spacetime metric endowed with the corrections jointly linked with Lorentz violation and NC spacetime effect. We examine the deviation of shape, and size of the ergosphere, energy emission rate, in this generalized situation. We also examine the influence of admis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 120 publications
0
1
0
Order By: Relevance
“…The first RRBH solution was found in 2019 by Ding et al [25], who showed that the bumblebee field can impact the properties of rotating black holes, including their shapes, sizes, and gravitational attraction. This was followed by several other studies that investigated the effects of rotation on bumblebee black holes, including their QNMs, GFs, shadow, superradiant instability, and many other features [5,23,28,29,32,34,36,[44][45][46][47][48][49][50].…”
mentioning
confidence: 98%
“…The first RRBH solution was found in 2019 by Ding et al [25], who showed that the bumblebee field can impact the properties of rotating black holes, including their shapes, sizes, and gravitational attraction. This was followed by several other studies that investigated the effects of rotation on bumblebee black holes, including their QNMs, GFs, shadow, superradiant instability, and many other features [5,23,28,29,32,34,36,[44][45][46][47][48][49][50].…”
mentioning
confidence: 98%